2005
DOI: 10.1038/nn1593
|View full text |Cite
|
Sign up to set email alerts
|

Classical and operant conditioning differentially modify the intrinsic properties of an identified neuron

Abstract: A long-standing debate in neuroscience is whether classical and operant conditioning are mechanistically similar or distinct. The feeding behavior of Aplysia provides a model system suitable for addressing this question. Here we report that classical and operant conditioning of feeding behavior differentially modify the intrinsic excitability of neuron B51, a critical element for the expression of the feeding response, thus revealing that these two forms of associative learning differ at the cellular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 12 publications
3
85
0
4
Order By: Relevance
“…Ideally, the question of whether classical and operant conditioning involve similar mechanisms should be addressed by analyzing both types of learning of the same behavior. This is becoming possible for feeding in Aplysia (Lechner et al, 2000a,b;Mozzachiodi et al, 2003;Brembs et al, 2004;Lorenzetti et al, 2006) and should now be possible for gill withdrawal as well.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the question of whether classical and operant conditioning involve similar mechanisms should be addressed by analyzing both types of learning of the same behavior. This is becoming possible for feeding in Aplysia (Lechner et al, 2000a,b;Mozzachiodi et al, 2003;Brembs et al, 2004;Lorenzetti et al, 2006) and should now be possible for gill withdrawal as well.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was demonstrated that different aspects of Aplysia feeding can be modified by food intake or buccal sensory nerve stimulation through classical or operant conditioning (Susswein et al, 1986;Lechner et al, 2000a,b;Brembs et al, 2002;Lorenzetti et al, 2006). Insights into the neuronal networks that generate Aplysia feeding, particularly those governing biting movements of the rasp-like radula, have derived from the use of isolated preparations of the buccal ganglia that contain the underlying motor circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…Successful swallowing is presumably signaled by the esophageal nerves. In other learning paradigms affecting Aplysia feeding, the esophageal nerves have a key role in learning (Nargeot et al 1997(Nargeot et al , 2007Lechner et al 2000;Mozzachiodi et al 2003;Brembs et al 2004;Lorenzetti et al 2006). In both classical and operant conditioning, esophageal nerve stimuli contingent on other stimuli lead to increased feeding.…”
Section: Learning With Edible Foodsmentioning
confidence: 99%
“…Classical and operant conditioning tasks depending on two contingent events affect Aplysia feeding (Nargeot et al 1997(Nargeot et al , 2007Lechner et al 2000;Brembs et al 2002Brembs et al , 2004Mozzachiodi et al 2003;Lorenzetti et al 2006). In these tasks, an unconditional stimulus or a reinforcer from the esophageal nerve is paired with a conditional stimulus or an operant, or with their neural analogs.…”
Section: Cellular Basis Of Learning a Triple Contingencymentioning
confidence: 99%
See 1 more Smart Citation